The National Heritage Of Ki Hadjar Dewantara In Taman Siswa About Culture-Based Education And Learning - Towaf, Siti Malikhah (KnE Social Sciences, 2017)
Global interdependence is a reality; in the security, economics, politics, socio-culture, and especially in the education of a nation. Relevant to the need for an international dialog on education, this study tries to explore: 1) the concepts of culture-based education and learning of Ki Hadjar Dewantara (KHD) in Tamansiswa, 2) the results of previous studies about the culture-based education and learning of KHD in Tamansiswa, and 3) the phenomena of Tamansiswa stagnancy as the national movement in education. A qualitative approach is used in this study. The researcher collected data from documents, observations, interviews; open ended questions. The data were analyzed to describe the focus of this study and get the conclusions. The result shows that Tamansiswa took role in culture-based education and learning by implementing Among System since the beginning of its history. The previous studies indicate that the KHD ideas are beyond his time and generation; very important for the nation in recent time. The phenomena of stagnancy is more due to management problems rather than the obsoleteness of philosophical foundation of Tamansiswa. It is necessary to socialize the concepts of culture-based education and learning of Ki Hadjar Dewantara (KHD) in Tamansiswa, to recognize the importance of KHD ideas as a contribution to the development of education in Indonesia. Keywords: National heritage, Culture-based Education, Tamansiswa.